Biopsychosocial Risk-factors Contributing to Intellectual Disability Among Children Attending Selected Special Schools - Henita Joshna Menezes; Judith Angelitta Noronha; Celastin Susan (Online Journal of Health & Allied Sciences, 2021)
Objective: To identify the biopsychosocial risk-factors that may contribute to Intellectual Disability (ID). Methods: Case-control study was conducted among 80 mothers of each of the institutionalized ID and normal children (6-15 years), at special schools/homes of ID children and children without ID, by using convenient sampling technique. Demographic proforma and a semi-structured questionnaire on biopsychosocial factors that may contribute to ID was used to collect the data. Results: Prenatal factors namely, history of drugs consumed during pregnancy, delayed cry soon after delivery, low birth weight babies, complications leading to NICU admission and various problems during pregnancy (P=0.015, 0.008, 0.013, 0.002, 0.056 respectively), the postnatal factor involving children who had head trauma (P=0.009) and social factor like family facing financial problems during delivery (P=0.011) were reported more by the mothers of ID children and were the main risk-factors that might have significantly contributed to the development of ID in children. Conclusion: Developmental delay characteristic of ID in children may be due to various biopsychosocial factors. Controlling these risk-factors has very significant implications in maternal and child health care preventive strategies.